Family History as a Risk Factor for Hypertension in The Coastal Area - N, Najihah; Handayani, Fitriya; AlDianto, Dicki; Iwan, Iwan (PT.Mantaya Idea Batara, 2023)
Hypertension is a serious medical condition and is a leading cause of premature death worldwide which significantly increases the risk of heart, brain, kidney and other diseases. However, not all hypertension sufferers are aware of the disease they suffer from and it is only discovered after complications occur. Therefore, hypertension must be prevented and controlled. Prevention and control of hypertension aims to prevent and reduce the probability of morbidity, complications and death. Hypertension can be prevented by controlling risk factors. This study aims to analyze the relationship between family history and the incidence of hypertension in the coastal communities of Tarakan City. This research is a quantitative study with a cross sectional study design. The sample in the research was the community in the working area of the Pantai Amal Health Center and met the sample criteria obtained using a purposive sampling technique. The data obtained was processed bivariately with the chi-square test. The results of the study showed a p value = 0.013, which means there is a relationship between family history and the incidence of hypertension. The conclusion of this study is that family history can be a risk factor for hypertension in the coastal area of Tarakan City. Therefore, it is hoped that health promotion efforts will take the form of scheduled education on hypertension risk factors and preventive efforts in the form of early detection so that people can prevent or control hypertension so that complications are avoided.